2019
DOI: 10.1002/gepi.22208
|View full text |Cite
|
Sign up to set email alerts
|

Exome chip‐driven association study of lipidemia in >14,000 Koreans and evaluation of genetic effect on identified variants between different ethnic groups

Abstract: Lipid levels in blood are widely used to diagnose and monitor chronic diseases. It is essential to identify the genetic traits involved in lipid metabolism for understanding chronic diseases. However, the influence of genetic traits varies depending on race, sex, age, and ethnicity. Therefore, research focusing on populations of individual countries is required, and the results can be used as a basis for comparison of results of other studies at the cross-racial and crosscountry levels. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…For example, in the Japanese population ( Tada et al, 2018 ), variants within the ABO gene have been identified as significantly modifying plasma lipoprotein metabolism, while “the usual suspects” (genes for SORT-1 , LDLR and HMGCR ) showed rather negligible effects. Importantly, identical variants could have different effects on plasma lipids and the frequencies of genetic variants can differ between different ethnicities ( Han et al, 2019 ); thus, a different gene score should be introduced for populations of different ethnic backgrounds.…”
Section: Ethnicity/population-specific Snpsmentioning
confidence: 99%
“…For example, in the Japanese population ( Tada et al, 2018 ), variants within the ABO gene have been identified as significantly modifying plasma lipoprotein metabolism, while “the usual suspects” (genes for SORT-1 , LDLR and HMGCR ) showed rather negligible effects. Importantly, identical variants could have different effects on plasma lipids and the frequencies of genetic variants can differ between different ethnicities ( Han et al, 2019 ); thus, a different gene score should be introduced for populations of different ethnic backgrounds.…”
Section: Ethnicity/population-specific Snpsmentioning
confidence: 99%